Informal Stroke Caregivers’ Satisfaction with Healthcare Services in a Tertiary Healthcare Centre in Ibadan, Nigeria (2014)
Background: Many of the consequences of stroke affect not only the stroke survivor but also the informal caregiver. Most studies on informal stroke caregivers in literature are on the effects of care giving on the physical, emotional and psychological well-being of these carers. Considering the important role informal caregivers play in the rehabilitation process of the stroke survivor, there is the need to consider their views and expectations from care received by their care recipients. Objectives: This study investigated the satisfaction of informal stroke caregivers with healthcare services being received by their care recipients in a tertiary hospital in Ibadan. Methodology: Fifty consenting informal caregivers (12 males, 38 females) of stroke survivors receiving in-patient care on the medical wards of a tertiary healthcare facility participated in this cross-sectional survey. A self-developed, 3-part questionnaire adapted from the Caregivers’ Satisfaction with Stroke Care Questionnaire was used for this study. Results: The data collected was summarized using descriptive statistics of mean and percentages and illustrated with pie charts. Most of the participants (44%) were children of the patients. The results obtained showed that 48% of the participants were highly satisfied, 48% were satisfied while only 4% reported dissatisfaction. Areas of dissatisfaction were quality of food, water supply, electricity supply, waiting time and information about the condition of their care recipients. Conclusion: This study showed that the extent of satisfaction of informal stroke caregivers with inpatient care at the University College Hospital was good. It has also shown the need to routinely assess the satisfaction of informal carers with services being provided in the hospital for the purpose of quality assurance.